Comparative study of straight and spiral earth air tunnel heat exchanger system operated in cooling and heating modes. (August 2017) - Mathur, Anuj; Priyam,; Mathur, Sanjay; Agrawal, G.D.; Mathur, Jyotirmay
Abstract: Thermal performance of Earth Air Tunnel Heat Exchanger (EATHE) system is found to be highly dependent on thermal properties of soil and soil with poor thermal properties require longer buried pipe for desired heat exchange between air and sub-soil. In densely populated country like India, EATHE systems are rarely used due to the limited ground space (higher aspect ratio in terms of length) in most of the residential and commercial applications. Therefore, in this paper, problem of space limitation for the installation of straight EATHE system is attempted by proposing new spiral shaped EATHE system. The developed EATHE systems were used to determine cooling and heating potential individually and COP were 5.94 and 6.24 in summer; 1.92 and 2.11 in winter for straight and spiral respectively. A transient numerical model has been developed to investigate the performance of both systems. The COP were 4.23 and 4.48 in summer; 5.0 and 5.16 in winter for straight and spiral respectively. The experimental and numerical results suggested that the thermal performance of these two systems are comparable can be interchanged based on available site conditions. Highlights: Development and experimental study of newly designed spiral EATHE system. The transient CFD model of Both EATHE systems were developed and validated. Straight and spiral EATHE system performances are comparable. Experimental COP of straight and spiral are 5.94 and 6.24 during summer respectively.